2022
DOI: 10.1186/s12888-022-04336-w
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and suicidal ideation in Chinese children and adolescents: the mediating role of mindfulness

Abstract: Background Childhood maltreatment (CM) has been associated with suicidal ideation (SI) in children and adolescents, yet the mediating role of mindfulness in this association remains unclear. This study aims to test the mediation of mindfulness in CM-SI association among a large sample of Chinese children and adolescents. Methods A population-based cross-sectional study of 3455 children and adolescents aged 10–17 years from southwest China Yunnan pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…This study indicated that initial levels of childhood maltreatment, peer victimization were positively related to initial levels of suicidal risk in adolescents, which aligned with previous research reporting that adolescents presented with higher levels of childhood maltreatment, peer victimization tend to show higher levels of suicidal risk (e.g., van Geel et al, 2022;Liang et al, 2022). Moreover, the current study also revealed that changes in childhood maltreatment, peer victimization were positively related to changes in suicidal risk.…”
Section: Direct Relationships Between Developmental Trajectories Of C...supporting
confidence: 89%
See 3 more Smart Citations
“…This study indicated that initial levels of childhood maltreatment, peer victimization were positively related to initial levels of suicidal risk in adolescents, which aligned with previous research reporting that adolescents presented with higher levels of childhood maltreatment, peer victimization tend to show higher levels of suicidal risk (e.g., van Geel et al, 2022;Liang et al, 2022). Moreover, the current study also revealed that changes in childhood maltreatment, peer victimization were positively related to changes in suicidal risk.…”
Section: Direct Relationships Between Developmental Trajectories Of C...supporting
confidence: 89%
“…Childhood maltreatment, encompassing physical abuse, emotional abuse, sexual abuse, and neglect endured by individuals below 18 years old (World Health Organization, 2006), has been posited as a vital contributor to suicidal risk in adolescents (Liang et al, 2022). Moreover, during adolescence, interpersonal relationships among adolescents transition gradually from being centered around parents to being centered around peers.…”
Section: Direct Relationships Between Childhood Maltreatment Peer Vic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Life adversities during critical developmental stages of life, especially childhood, are associated with more severe and persistent symptoms that negatively affect health outcomes [ 50 ]. In addition, it is reported that physical abuse could increase the risk of suicide tendency in adolescents [ 51 ], young people [ 52 ], persons with MDD [ 53 ], bipolar disorder [ 54 ], midlife [ 55 ], and veterans [ 42 ], indicating that childhood physical trauma experiences have a strong impact on suicide risk. The results from our study are in accordance with prior studies, wherein a history of exposure to childhood physical abuse was significantly associated with suicidal behaviors.…”
Section: Discussionmentioning
confidence: 99%